Trading for speculators: The role of physical actors in the financialization of coffee, cocoa and cotton value chains - Bernhard Tröster; Ulrich Gunter (Austrian Foundation for Development Research (ÖFSE), 2022)
The prices of cash crops are crucial to the livelihood of millions of households in developing countries. While the influence of financial investors on the determination of global commodity prices on derivative exchanges is extensively discussed, the role of physical actors in the global value chains (GVCs) is largely disregarded in the 'financialization of commodities' debate. This excludes, however, the interlinked activities of GCV lead firms in financial and physical commodity markets, by which prices are transmitted to producer countries. We, therefore, relate the buying and pricing strategies of lead firms in the coffee, cocoa and cotton GVCs with their activities as hedgers on commodity derivatives markets. Based on Open Interest (OI) data in the Commitments of Traders (COT) database, a measure of buying and selling pressure by trader categories is applied in a GARCH model. Our findings show that liquidity provision by hedgers allows speculators' position takings to drive returns of global benchmark prices. We identify elaborated financial hedging and physical price-setting strategies as a determinant of hedgers' activities on derivative markets, which contributes to price transmission through GVCs and thereby expose smallholder and other actors in cash crops in producer countries to price risks.
Keywords: 330; Financialization; Cash crops; Price transmission; Global Value Chains; Hedging; GARCH Models